2003
DOI: 10.1038/sj.onc.1206657
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific immunity does not mediate acute regression of UVB-induced p53-mutant clones

Abstract: Chronic irradiation of human or murine epidermis with ultraviolet B (UVB) induces clones of p53-mutant keratinocytes. Clones precede and parallel the induction of carcinomas, suggesting that they are an early stage of UVB carcinogenesis. In the absence of UVB, these clones rapidly regress. For UVB-induced murine skin tumors and papillomas, regression is known to involve antigen-specific immunity. To determine whether antigen-specific immunity influences the creation, expansion, or regression of p53-mutant clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…However, in both UV regimens, p53-positive clones were still detectable for as long as 8 weeks after the last UV radiation exposure (Berg et al, 1996). Similarly, Remenyik et al (2003) found that approximately 50% of p53-positive keratinocyte clones in C57Bl/6 mouse skin disappeared within 2 weeks after discontinuation of UV treatment (37 or 47 kJ/m 2 total UV). In our experiments, there was a slight decrease in the incidence of p53 R270C mutations at 22 weeks after UV radiation discontinuation, but it was not statistically significant.…”
Section: ) Previous Studies Havementioning
confidence: 87%
See 4 more Smart Citations
“…However, in both UV regimens, p53-positive clones were still detectable for as long as 8 weeks after the last UV radiation exposure (Berg et al, 1996). Similarly, Remenyik et al (2003) found that approximately 50% of p53-positive keratinocyte clones in C57Bl/6 mouse skin disappeared within 2 weeks after discontinuation of UV treatment (37 or 47 kJ/m 2 total UV). In our experiments, there was a slight decrease in the incidence of p53 R270C mutations at 22 weeks after UV radiation discontinuation, but it was not statistically significant.…”
Section: ) Previous Studies Havementioning
confidence: 87%
“…In hairless mouse skin, UV-induced p53 mutations could be detected by AS-PCR as early as 1 week after the first UV radiation exposure, with 80-90% of animals incurring p53 mutations after 8 weeks of UV treatment (Ouhtit et al, 2000a). Clones of keratinocytes carrying mutant p53 have also been detected in mouse skin within 2-3 weeks after UV treatment (Berg et al, 1996;Rebel et al, 2001;Remenyik et al, 2003). In this study, we investigated the fate of p53 mutations and the development of skin cancer after discontinuation of UV treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations